Coordination Patterns of the Swimming Start: A Comparative Study Between Elite and Sub-Elite Swimmers. - Lin, Yi; Li, Shudong; Yang, Luqi; Zhou, Zhanyi; Baker, Julien S.; Gu, Yaodong (Journal of Sports Science & Medicine, 2025)
This study investigated upper-lower body coordination during the swimming start. Coupling angle mapping was applied to assess segmental dominance, coupling angle, and coupling angle variability across four dive-start phases in elite and sub-elite swimmers. Data were collected from twenty swimmers (ten elite and ten sub-elite), based on their three fastest maximal-effort dive starts. The continuous entry movement from air to water was captured in detail using a high-speed multi-camera system positioned above and below the water. Results demonstrated that coordination patterns varied across the four phases, with high similarity when the thigh dominated, such as during the flight phase. Notably, coordination during the on-block phase differed significantly prior to hand-off. Elite swimmers exhibited greater trunk dominance in the entry phase, facilitating a more horizontal dive-in, whereas sub-elite swimmers showed trunk dominance later, during the transition phase. In conclusion, the time required to reach a specific distance or phase does not necessarily indicate superior start performance. Swimmers must balance drag minimization during the dive-in trajectory with rapid entry to initiate stroking. All swimmers maintained a streamlined posture and predominantly employed thigh-dominant strategies, while variations in trunk-dominant coordination were observed during entry and transition phases. Occasional high coupling angle variability in elite swimmers may reflect individualized coordination strategies. These findings highlight the importance of individualised training to optimize start performance.